2015
DOI: 10.1007/s00227-015-2664-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predators on sea urchin density and habitat use in a southern California kelp forest

Abstract: understory algal cover during the day, but not during the night. Examining whether urchin mortality from predation is density dependent and how habitat complexity influences this relationship is imperative because behavioral changes and increases in urchin populations can have vast ecological and economic consequences in kelp forest communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
3
13
1
Order By: Relevance
“…This level of variability is similar to that previously documented in this system (Nichols et al. ), and is likely due to rapid, localized responses of fish predators to urchin prey in some cases. Overall, our results suggest a need to reevaluate the paradigm of top‐down control on SC rocky reefs in the absence of sea otters.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This level of variability is similar to that previously documented in this system (Nichols et al. ), and is likely due to rapid, localized responses of fish predators to urchin prey in some cases. Overall, our results suggest a need to reevaluate the paradigm of top‐down control on SC rocky reefs in the absence of sea otters.…”
Section: Discussionsupporting
confidence: 88%
“…However, sheephead and other predators only regulated purple urchins when large red urchins were absent, a condition consistent with fished areas but not typically observed within MPAs (Nichols et al. , Teck et al. ).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In affected areas, urchins may persist for years after consuming the canopy algae, just by living on biofilms, drifting macroalgae and algal recruits, while maintaining the barren ground (Leinaas and Christie 1996). Without exaggeration, the macroalgal/urchin system constitutes a central corner-stone for the conceptual development of community ecology (e.g., Paine and Vadas 1969;Mann 1977;Paine 1980;Estes et al 1998) and various aspects of the topic are frequently reported in this journal (some recent papers include, e.g., Fagerli et al 2015;Nichols et al 2015). However, to this very day, there are still apparent gaps in our knowledge regarding many of the processes and mechanisms involved in defining the two alternative stable states of these ecosystems (Filbee-Dexter and Scheibling 2014; Ling et al 2015).…”
Section: Nos Numerus Sumus Et Fruges Consumere Natimentioning
confidence: 99%